An innovative approach for green synthesis of iron oxide nanoparticles: Characterization and its photocatalytic activity. (1st December 2018) - Arularasu, M.V.; Devakumar, J.; Rajendran, T.V.
Graphical abstract: Morphology of synthesized Fe3 O4 NPs products spherical morphology may be owing to following reasons. (i) Fe3 O4 cubic structure has basal polar oxygen face and a top the corner-exposed polar metal (M 2+ ) face therefore they have distinct reactivity and charge, positively development of spherical particles (ii) particularly catch up of glycine molecules on Fe3 O4 crystals, favoring formation of spherical particles (iii) the nitro group in glycine in relatively high polar molecule, could effectively attach to the surface of Fe3 O4 crystals. This interaction could promote preferential growth of Fe3 O4 crystal growth and cause of spherical particles. Abstract: The catalytic and biological properties of metal oxide nanoparticles with the biosynthesis green technology begin to allow for continuing growth of nanotechnology. Natural extracts provide a great alternative to harsh chemical, efficient synthesis techniques and cost effective. Here, Fe3 O4 nanoparticles were synthesized via Kappaphycus alvarezii plant extract green method with efficient hot plate combustion method. The synthesized nanomaterials characterized by X-ray diffraction (XRD), energy dispersive X-ray analysis (EDX), Fourier transform infrared (FTIR) spectroscopy. The shape and exceptional size of synthesized Fe3 O4 nanoparticles demonstrated using high resolution scanning electron microscopy (HRSEM) and transmission electron microscopy (HRTEM). Fe3 O4 nanoparticles were investigated in different applications, for example, photocatalytic degradation of hazardous cationic textile dye waste (CTDW) collected from dyeing industry. Furthermore, antibacterial activity of Fe3 O4 nanoparticles against Gram positive ( Staphylococcus aureus ) and Gram-negative ( Escherichia coli ) bacteria and also, evaluate the impedance analysis. Fe3 O4 have been reported earlier, but due to their high cost and toxic chemical used they needed to be modified by cost effective material and biosynthesis. Possible reaction mechanism pathways during photocatalyst into the dye solution over Fe3 O4 nanoparticles have been proposed. The results explained that the synthesis of Fe3 O4 nanoparticles was economically cheap when compared with conventional methods and the nanoparticles showed a high efficiency in the removal of hazardous textile dyes, in an eco-friendly manner. Thus we have projected a diverse approach for the green synthesis of Fe3 O4 NPs, which is economical and that is extremely important in the present times for the removal of hazardous chemicals.